PERILAKU HIDUP BERSIH DAN SEHAT DI DESA TULEHU PADA MASA PANDEMI COVID-19 - Ode Rachmi; Dwight Nusawakan; Abdul Thalib; Lintje Sintje Corputty (Pasapua Health Journal, 2022)
Introduction: Clean and healthy living behavior is all health behavior that is carried out on the basis of a person’s awareness so that he can handle himself in terms of health and can handle himself in terms of health and can play an active role in health activities both for individuals and for others . Method: The type of research conducted in this research is qualitative research using a phenomenological approach. In this study, 10 people from RT 001 Hamlet of Mangga Tree, Tulehu Village became informants. This research was conducted using the interview method, data collection tools in the form of recordings, cameras, stationery and interview guides. Results: The results of this study show that there are 3 factors that have been examined, namely based on natural factors, that 10 informants already know the importance of complying with health protocols and implementing clean and healthy living behaviors during this pandemic. Based on planned change factors, it is important to implement clean and healthy living behaviors for individuals to prevent and protect themselves from the spread of COVID-19. Based on the willingness to change factor, there is a change in awareness and own desire to implement health protocols and clean and healthy living behavior during the COVID-19 pandemic. Conclusion: This study shows that there are changes in clean and healthy living habits during the COVID-19 pandemic in the community, namely complying with health protocols, and maintaining clean and healthy living behaviors during the COVID-19 pandemic to avoid the spread of COVID-19.